Challenging corporate commitment to CSR: Do CEOs keep talking about corporate social responsibility (CSR) issues in times of the global financial crisis?. Issue 11 (21st November 2016) - Fehre, Kerstin; Weber, Florian
Abstract : Purpose: In times of crisis, the fundamental principles of companies erode, leading to strategy shifts. This paper aims to examine whether corporate social responsibility (CSR) is on management's agenda in times of crisis, indicating CSR embeddedness into corporate strategy. The focus is on the four pillars of CSR: social, environment, economy and governance. Design/methodology/approach: Starting points are competing hypotheses based on shareholder and stakeholder theory. Chief executive officer (CEO) letters to shareholders of German HDAX firms from 2003 to 2012 are analyzed by means of computer-aided text analysis. Findings: The authors find that CEOs talk less about CSR in times of crisis, especially about social and governance issues, indicating that CSR is not fully embedded into corporate strategy, and that, in times of crisis, other aspects gain more importance on management's agenda. Research limitations/implications: CEO communication is an indicator for management's attention. Less talk about CSR in times of crisis does not automatically indicate less real CSR activity. This study is a starting point for analyses of the discrepancy between both, if any exists. Practical implications: Managers should regard CSR as a strategic and trust enhancing element and stick to CSR even when under pressure from market distortions. Social implications: Environment issues – exposed to companies' attention for a long time – are embedded into corporate strategy. More research and management attention is essential to get the other CSR aspects woven into company DNA as well. Originality/value: The paper is the first to research CSR in times of crisis in depth: CSR as umbrella covers social, environment, economy and governance issues. The institutional level of analysis ensures that implications for the business-society link are central.